Discrimination, quotas, and stereotypes - Lennart Struth; Max Thon (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
We analyze the effect of employment-quota policies on the development of uncertainty and stereotypes in a model of inaccurate statistical discrimination with ambiguity about worker abilities. We show that, even if group characteristics are identical, higher uncertainty about one group can result in discriminatory employment decisions. The success of a quota in correcting the beliefs then depends crucially on the firm's learning process. In particular, we find that the more confident the firm is in its initial priors, the longer a quota needs to be implemented until beliefs are sufficiently corrected such that discriminatory behavior vanishes.
Keywords: J71; K31; M51; D81; 330; Statistical discrimination; stereotypes; quotas; ambiguity